1997
DOI: 10.1177/107110079701800905
|View full text |Cite
|
Sign up to set email alerts
|

Primary Repair Without Augmentation for Early Neglected Achilles Tendon Ruptures in the Recreational Athlete

Abstract: From 1987 to 1994, the senior author performed 41 Achilles tendon repairs. We identified 11 patients during this period (age, 35.3 years; range, 26-60 years) who fit the criterion for neglected Achilles tendon rupture (repair > or = 4 weeks and < or = 12 weeks from injury). All patients underwent proximal release of the gastrocsoleus complex, imbrication of the early fibrous scar without excision of any local tissue, and primary repair of the tendinous ends with two No. 5 Ticron sutures (5R, 6L). Several (thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…In our series, fibrous scar tissue of AT stumps was preserved to restore some thickness with suture on the FHL transfer. Preserving this interposition scar tissue between tendon stumps has been shown to have the capacity to form tendon-like repair tissue, and previous studies concluded that it is suitable for repairing chronic AT ruptures [20,29]. Similarly, in a recent study, Lee et al showed on histological examination of fibrous scar stump biopsies that this tissue was composed of thick collagen fibers running parallel to the tendon axis with highly cellular fibrovascular tissue, altogether improving tendon healing [15].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, fibrous scar tissue of AT stumps was preserved to restore some thickness with suture on the FHL transfer. Preserving this interposition scar tissue between tendon stumps has been shown to have the capacity to form tendon-like repair tissue, and previous studies concluded that it is suitable for repairing chronic AT ruptures [20,29]. Similarly, in a recent study, Lee et al showed on histological examination of fibrous scar stump biopsies that this tissue was composed of thick collagen fibers running parallel to the tendon axis with highly cellular fibrovascular tissue, altogether improving tendon healing [15].…”
Section: Discussionmentioning
confidence: 99%
“…These delays reportedly compromise the end clinical result [4,5,7,18,21,22]. If an acute rupture is missed and becomes chronic, there is 20% less endurance of the muscle and the treatment becomes more difficult [19].…”
Section: Discussionmentioning
confidence: 99%
“…Delay in treatment, whether operative or nonoperative, reportedly has detrimental effects on the final outcomes [4,5,7,18,21,22]. Therefore, it is important to accurately diagnose an acute injury and begin the treatment early.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors propose the complete excision of the degenerative Achilles due to better pain relief [4]. In recent series, however, preservation of the fibrous scar tissue has been suggested to make the tendon length assessment easier and the scar tissue is thought to work as a scaffold for the transferred FHLT [5,6,8].In fact, this scar tissue has been shown to have the capacity to form a tendon like repair tissue [16][17][18]. In our study, the tendon stumps were preserved, and possible deficits were bridged with single strand of FHL tendon only.…”
Section: Discussionmentioning
confidence: 99%
“…No failure of the FHLT transfer occurred during the follow-up period. Also all previous studies with FHLT transfer, despite the single or double incision technique, preserving or not the scar tissue, have shown very low failure rates [5,6,8,9,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%